Cell Cycle Analysis Using In Vivo Staining of DNA-Synthesizing Cells - Páral, Petr; Báječný, Martin; Savvulidi, Filipp; Nečas, Emanuel (Methods in molecular biology, 2020)
The thymidine analogues BrdU (5-bromo-2´-deoxyuridine) and EdU (5-ethynyl-2´-deoxyuridine) are routinely used for determination of the cells synthesizing DNA in the S-phase of the cell cycle. Availability of the anti-BrdU antibody clone MoBu-1 detecting only BrdU allowed to develop a method for the sequential DNA labelling by these two thymidine analogues for determining the cell cycle kinetic parameters.In the current step-by-step protocol, we present` two approaches optimized for in vivo study of the cell cycle and the limitations that such approaches imply: (1) determination of the cell flow rate into the G2-phase by dual EdU/BrdU DNA-labelling method and (2) determination of the outflow of DNA-labelled cells arising from the mitosis.
Keywords: Animals; Bromodeoxyuridine; průtoková cytometrie; Cell Cycle; buňky kostní dřeně; Staining and Labeling; DNA; buněčná diferenciace; Rheology; S Phase; Mice; Deoxyuridine; Flow Cytometry; barvení a značení; analýza dat; myši; Immunophenotyping; Mitosis; buněčný cyklus; mitóza; imunofenotypizace; reologie; Bone Marrow Cells; Cell Differentiation; deoxyuridin; bromodeoxyuridin; S fáze; zvířata; Data Analysis